Effect of irrigation on growth and establishment of young rubber plants in a humid tropical region of India - Lakshmanan R; Chandrasekhar T R; Edathil T T; Reghu C P (Natural Rubber Research, 2007)
In an experiemnt to study the growth response of young rubber during the initial three years to varying levels of irrigation, plant girth and girth increment were on par with irrigation at 1.2, 0.9 and 0.6 IW/CPE ratio and significantly superior to that of the control and irrigation at IW/CPE ratio of 1.2, 0.9, 0.6 and 0.3 during the period from December to May exhibited a girth increment that was 84, 67, 49 and 46 per cent higher than that of the corresponding girth increment observed during the monsoon season. In the unirrigated treatment this was only 38 per cent. A significant increase in RGR was observed for the treatments irrigated at IW/CPE ratio of 1.2 and 0.9 over that of the other treatments. Consumptive use and the ratio of consumptive use to pan evaporation were also worked out.
Source Year: 2007
Keywords: Girth; Girth; Immature rubber; Immature rubber; Irrigation; Irrigation; IW/CPE ratio; IW/CPE ratio; Relative growth rate; Relative growth rate